Regional financial inclusion and poverty: Evidence from Indonesia - Iwan Fathi Fauzan; Muhammad Firdaus; Sahara Sahara (Economic Journal of Emerging Markets, 2020)
This paper builds a financial inclusion index of thirty-three provinces in Indonesia from formal financial institutions banks. It aim at analyzing how the financial inclusion index relates to regional poverty using a spatial panel econometric approach. Findings/Originality: The results show that the average financial inclusion index of each province in Indonesia is still in a low category, and there is a financial system development inequality between DKI Jakarta Province and other regions. We also find that poverty has a significant negative effect on the financial inclusion index. With the recent migration of residents as a spatial weighting matrix, we decompose the global effect of the poverty variable on the financial inclusion index into a local effect for each province.